Peran Teknologi Digital dalam Meningkatkan Efektivitas Operasional UMKM - Harefa, John Fiser; Zebua, Dermawan (CV. SINAR HOWUHOWU, 2026)
This study examines the role of digital technology in enhancing the operational effectiveness of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. The research focuses on how the adoption of digital technology and management information systems contributes to improving operational efficiency, decision-making processes, and competitiveness in an increasingly competitive business environment. A descriptive qualitative approach is employed to gain an in-depth understanding of digital transformation practices within MSME operations. The findings reveal that digital technology facilitates business process automation, fosters innovation in products and services, expands market reach, and strengthens relationships with customers and business partners. Nevertheless, the adoption of digital technology among MSMEs has not yet reached its full potential due to challenges such as inadequate digital infrastructure, limited digital literacy and skills of human resources, and unequal access to technology. The study concludes that digital technology represents a strategic resource capable of enhancing MSME operational effectiveness and competitiveness when supported by adequate infrastructure and skilled human resources.